Becoming Biosubjects : Bodies. Systems. Technology. - Gerlach, Neil, 1963- (Book collections on Project MUSE., 2011)
Focusing on four major issues, the authors examine the ways in which genetic technologies are shaping criminal justice practices, how policies on reproductive technologies have shifted in response to biotechnologies, the debates surrounding the patenting of higher life forms, and the Canadian (and global) response to bioterrorism. Regulatory strategies in government and the courts are continually evolving and are affected by changing public perceptions of scientific knowledge. The legal and cultural shifts outlined in Becoming Biosubjects call into question what it means to be a Canadian, a citizen, and a human being."--Pub. desc